2018
DOI: 10.1002/mds.27601
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2‐mediated Rab10 phosphorylation in immune cells from Parkinson's disease patients

Abstract: Background Leucine‐rich repeat kinase 2 is a potential therapeutic target for the treatment of Parkinson's disease, and clinical trials of leucine‐rich repeat kinase 2 inhibitors are in development. The objective of this study was to evaluate phosphorylation of a new leucine‐rich repeat kinase 2 substrate, Rab10, for potential use as a target engagement biomarker and/or patient enrichment biomarker for leucine‐rich repeat kinase 2 inhibitor clinical trials. Methods Peripheral blood mononuclear cells and neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 39 publications
12
94
1
Order By: Relevance
“…Consistent with our data, they reported no differences in pS935 or total LRRK2 levels in iPD subjects compared to healthy controls. On the other hand, Atashrazm et al [15] reported higher levels of total LRRK2 levels in neutrophils from iPD cases compared to healthy controls. The apparent discrepancy between our study and [15] may be due to previously reported cell-specific regulation of LRRK2 expression [16,17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with our data, they reported no differences in pS935 or total LRRK2 levels in iPD subjects compared to healthy controls. On the other hand, Atashrazm et al [15] reported higher levels of total LRRK2 levels in neutrophils from iPD cases compared to healthy controls. The apparent discrepancy between our study and [15] may be due to previously reported cell-specific regulation of LRRK2 expression [16,17].…”
Section: Discussionmentioning
confidence: 96%
“…There is only one previous report [15] on levels of pS935 and total LRRK2 in PBMCs, but these assessments were restricted to iPD and healthy controls. Consistent with our data, they reported no differences in pS935 or total LRRK2 levels in iPD subjects compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 expression has also been linked with Mycobacterium tuberculosis infection (Härtlova et al, 2018;Wang et al, 2018). LRRK2 is expressed in a variety of cell lineages, including several immune subsets, notably B cells, neutrophils, monocytes, macrophages and microglia (Atashrazm et al, 2018;Fan et al, 2018;Gardet et al, 2010;Hakimi et al, 2011;Kim et al, 2012;Marker et al, 2012;Moehle et al, 2012;Thévenet et al, 2011) (reviewed in (Lee et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently identified a subset of Rab GTPases (Rab3A/B/C/D, Rab5A/B/C, Rab8A/B, Rab10, Rab12, Rab29, Rab35, and Rab43) as LRRK2 substrates 8,9 . Among these, Rab10 appears to be a key physiological kinase substrate [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%